PERSEPSI GURU TENTANG KOMPETENSI MANAJERIAL KEPALA SEKOLAH DASAR WILAYAH SATU KEPENGAWASAN KECAMATAN NATAL KABUPATEN MANDAILING NATAL - Mukti Kanaya Sidiq; Maisyaroh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine teachers’ perceptions of the managerial competence of elementary school principals in Supervisory Area One, Natal Subdistrict, Mandailing Natal Regency. This research employed a descriptive research design with a quantitative approach. The instrument used to collect the data was a validated questionnaire consisting of 48 items. The respondents of this study were 78 teachers selected using a total sampling technique. The distribution of respondents by school was as follows: SDN 363 Taluk Sikara-Kara (8 teachers), SDN 367 Pardamean Baru (8 teachers), SDN 368 Kampung Sawah (6 teachers), SDN 372 Sikara-Kara I (9 teachers), SDN 373 Sikara-Kara II (8 teachers), SDN 378 Sikara-Kara IV (8 teachers), SDN 379 Sikara-Kara III (8 teachers), SDN 380 Kun-Kun (4 teachers), and SDS Bina Artha Mahkota (19 teachers). Data were collected using questionnaires, and the data analysis technique applied was descriptive quantitative analysis. The results of the study indicate that teachers’ perceptions of the managerial competence of elementary school principals in Supervisory Area One, Natal Subdistrict, Mandailing Natal Regency fall into the very high category with an overall mean score of 3.26. Based on each indicator, the results are as follows: (a) school planning (3.29); (b) school organizational development (3.37); (c) utilization of school resources (3.24); (d) management of change and school development (3.39); (e) creation of school culture and climate (3.24); (f) management of teachers and staff (3.20); (g) management of school facilities and infrastructure (3.36); (h) management of school–community relations (3.41); (i) student management (3.27); (j) curriculum development management (3.38); (k) school financial management (3.38); (l) school administrative management (3.24); (m) management of special service units (3.06); (n) school information system management (3.16); (o) utilization of technological advancements (3.09); and (p) monitoring, evaluation, and reporting of school program implementation (3.18).